Planar broadband slotted two-ring antenna for mobile communication of the fifth generation radiation - Цалиев, Т.А. (Radiotekhnika, 2019)
The topology of the planar broadband slotted two-ring antenna is presented and frequency dependences of its electrodynamic characteristics, which are compared with similar characteristics of the slit antenna of "dumbbell" type, are given. The results of computer simulation for these antennas in the form of distributions of the electric field strength in the near field are also shown. The antenna of the proposed shape and geometric dimensions can be referred to the broadband class. The working frequency band, determined by both the directivity and the reflection coefficient at the input, can include simultaneously all the areas of promising mobile communication standards of the fifth generation. Broadband properties of this antenna are due to the presence in its design of two broad partially crossed planar rings and a narrow relatively short slit, which is the area of their intersection. Along with the broadband, the advantages of such an antenna element are: an increased value of the directivity as compared to dipole and slot antennas, as well as manufacturability, which gives a certain benefit in mass production.